Crecimiento de Colossoma macropomum en estanques de tierra en dependencia de la densidad. (ING) - Günther, Jorge (1997)
The effects of density (range 0.5 to 2 fish/m2) on the culture of tambaquí, Colossoma macropomum, in earthen ponds and fed a 35% protein diet, were assessed. No statistical differences were found in growth and feed utilization between densities. The growth performance of tambaquí in 60 m2-ponds was, however, much worse than in another growth cycle performed simultaneously under the same conditions in a 3000 m2 pond. It is hypothesized that the growth rate of tambaquí is strongly related to the size of the pond.